Bonding quality of plywood with Cupressus lusitanica Mill. Wood - Modes, Karina Soares; Cozer, Vitoria; Cunha, Alexsandro Bayestorff da; Dobner Júnior, Mario; Vivian, Magnos Alan (Revista de Ciências Agroveterinárias, 2025)
The state of Santa Catarina occupies a prominent position in national exports of coniferous plywood and whose production is highly dependent on pine wood. With a view to expanding the possibilities of including new raw materials in this segment, the study aimed to evaluate the quality of gluing plywoods made with C. lusitanica wood veneers and its combination with P. taeda wood and compare performance with panels composed only of P. taeda and with the requirements stipulated for Pine plywood by the National Wood Quality Program (PNQM). Panels with 17 mm thick, glued with phenolic resin at a amount of adhesive of 328 g/m², consolidated in a press at a temperature of 135 ºC and specific pressure of 12 kgf/cm² were evaluated for the quality of the bondline upper, central and lower by the shear strength test after basic and additional pre-treatments for gluing classes 2 and 3. It was observed that the raw material did not influence the average shear stress of the plywoods produced and the quality of the gluing between the gluelines, and attended the average shear resistance for pine plywoods with similar characteristics by PNQM, with the exception of panels resulting from the mix of the species C. lusitanica and the species P. taeda, after pre-treatment “BDB”. The use of C. lusitanica wood resulted in pannels with gluing quality equivalent to that obtained for P. taeda panels and could be an option to be introduced in the plywood panel segment, without the need to adapt to the already consolidated manufacturing process for the plywoods of P. taeda.